Wheat subsidies, wheat markets and food security in Sudan: Current state and options for the future - Abay, Kibrom A.; Abdelaziz, Fatma; Abdelfattah, Lina Alaaeldin; Breisinger, Clemens; Dorosh, Paul A.; Resnick, Danielle; Siddig, Khalid; William, Amy (International Food Policy Research Institute, 2022)
This policy note summarizes the key findings from the following four research papers prepared by the International Food Policy Research Institute with financial support by the United States Agency for International Development (USAID): 1. Bottlenecks in Sudan’s Wheat Value Chains: Insights from Surveys 2. Evaluating Cereal Market (Dis)Integration in Sudan 3. Distributional Consequences of Wheat Policy in Sudan: A Simulation Model Analysis 4. Political Economy of Wheat Value Chains in Post-Revolution Sudan